1997
DOI: 10.1002/(sici)1521-186x(1997)18:1<25::aid-bem5>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of weak electromagnetic field on ionic currents in aqueous solutions of amino acids

Abstract: To analyze the mechanisms of action of weak electric and magnetic fields on ion motion in solution, a new approach is outlined allowing for collective interactions of large ionic ensembles with the external field. Bioelectromagnetics 18:25–27, 1997. © 1997 Wiley‐Liss, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Del Giudice et al [ 31 ] propose a two phase state of water with regions providing quantum coherence, and thereby a decoupling factor against the surrounding thermodynamical equilibrium. Already earlier Novikov et al [ 32 ] suggested a self-organizing mechanism for larger ion assemblies and substantiated this theory by applying motion equations for basic forces of only ~10 -21 – 10 -25 N for the Lorentz ean force on an ion from an external magnetic field. Further, the coupling of electron spin states for comparably long distances and time windows could provide a resonant EMF effect for radical pairs [ 33 ], representing a special case of the common radical pair effect and enhancing its sensitivity for EMF by orders of magnitude.…”
Section: Discussionmentioning
confidence: 90%
“…Del Giudice et al [ 31 ] propose a two phase state of water with regions providing quantum coherence, and thereby a decoupling factor against the surrounding thermodynamical equilibrium. Already earlier Novikov et al [ 32 ] suggested a self-organizing mechanism for larger ion assemblies and substantiated this theory by applying motion equations for basic forces of only ~10 -21 – 10 -25 N for the Lorentz ean force on an ion from an external magnetic field. Further, the coupling of electron spin states for comparably long distances and time windows could provide a resonant EMF effect for radical pairs [ 33 ], representing a special case of the common radical pair effect and enhancing its sensitivity for EMF by orders of magnitude.…”
Section: Discussionmentioning
confidence: 90%
“…For example, this ratio in Zhadin's work on amino acids [Novikoff and Zhadin, 1994] was .002. This is hard to explain using the PRM model, since the Bessell function J n (nB/B o ) appearing in Eq (15) tends towards zero for vanishingly small values of the ratio B/B o .…”
Section: Ion Parametric Resonancementioning
confidence: 99%
“…We could thus speculate that transmission of this ordering principle was electromagnetic (EM) in nature. Furthermore, it is not insignificant that a growing number of observations suggest the susceptibility of biological systems or water to electric and low-frequency electromagnetic fields (Tsonga, 1989;Frey, 1993;Blanchard et al, 1994;Novikov et al, 1997;Vallée et al, 2005). Together, these considerations informed exploratory research which led us to speculate that biological signalling might involve low frequency waves potentially transmissible to cells or water by purely electromagnetic means.…”
Section: An Alternate Model To Explain the Extent Of Non-bulk-like Wamentioning
confidence: 99%